2016
DOI: 10.1007/s00411-016-0640-y
|View full text |Cite
|
Sign up to set email alerts
|

Variation of indoor radon concentration and ambient dose equivalent rate in different outdoor and indoor environments

Abstract: Subject of this study is an investigation of the variations of indoor radon concentration and ambient dose equivalent rate in outdoor and indoor environments of 40 dwellings, 31 elementary schools and five kindergartens. The buildings are located in three municipalities of two, geologically different, areas of the Republic of Macedonia. Indoor radon concentrations were measured by nuclear track detectors, deployed in the most occupied room of the building, between June 2013 and May 2014. During the deploying c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…In both cases, the coeffi cient of variation and geometric standard deviation have high values. The reasons for dispersions between schools are the variability of the factors that controls indoor Rn, namely the geogenic Rn potential (different geological base) and building characteristics in terms of Rn infi ltration and accumulation [4]. Furthermore, the results from both detectors have about the same distribution (Fig.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…In both cases, the coeffi cient of variation and geometric standard deviation have high values. The reasons for dispersions between schools are the variability of the factors that controls indoor Rn, namely the geogenic Rn potential (different geological base) and building characteristics in terms of Rn infi ltration and accumulation [4]. Furthermore, the results from both detectors have about the same distribution (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…The estimated values of the relative combined uncertainty of individual results in this study, which include uncertainties of track counting, time, calibration factor, and the detector background, were in the range 11 to 19%. This type of detector is also used in other scientifi c research [3,4].…”
Section: Methodsmentioning
confidence: 99%
“…The results of annual CRn measurements in schools, dwellings and kindergartens were not different (Stojanovska et al, 2016a). There are also no differences between the results of CRn in schools when they are based on the annual measurements (12 months) and when they are in the period exempt from the summer holiday (9 months) (Stojanovska et al, 2016b).…”
Section: Building Factors Affecting Radon Variabilitymentioning
confidence: 81%
“…The analysis showed that the CRn in buildings with new windows was twice higher in comparison to CRn in buildings with wooden windows (GM = 110 (2.13) Bq/m 3 ). In the same survey, the environmental impact on CRn was examined, but it turned out that there was no difference between urban and rural areas (Stojanovska et al 2016a).…”
Section: Building Factors Affecting Radon Variabilitymentioning
confidence: 99%
“…The higher levels of background radiation are associated with volcanic rock masses (granite), and lower levels with sedimentary rocks (Stojanovska et al, 2016;Abba et al, 2017) and Quaternary geological background (Sanusi et al, 2014).…”
Section: Physicsmentioning
confidence: 99%